Tanggung Jawab Notaris dalam Membuat Covernote Sebagai Jaminan Atas Utang - Alini, Aulia Meyritza; Raffles, Raffles; Aulia, M. Zulfa (Universitas Batanghari Jambi, 2025)
The purpose of this research is to analyze the legal responsibility of Notaries in creating cover notes as collateral for land title certificates. Covernote, when viewed from the perspective of formal civil law, does not actually have the binding force of a deed made by a notary, because a covernote is not a legal product of a notary and is not regulated under positive law in Indonesia. This type of research is normative, with data collection techniques through literature study, and analyzed qualitatively. The research results show that the notary's responsibility in the covernote is limited to the period when the document handled by the notary is still in the processing stage, such as in the case of the registration process of encumbering rights. If the process of registering the encumbrance of the mortgage handled by the notary is completed until the issuance of the mortgage certificate, then the previous covernote will be replaced by the mortgage certificate that has been processed by the notary as the actual form of guarantee. Covernote is not a proof of collateral but merely serves as a temporary or provisional document, which acts as a basis for the bank that will eventually disburse the loan application. The notary's duty in draughting a covernote as a debt guarantee is to uphold the highest standards of honesty, integrity, impartiality, and diligence in verifying the authenticity of the information provided in the debt guarantee documents in order to avoid any legal ramifications..